The Effect of Kahoot Application in the Quality to Students' Writing(Quasi-Experimental design in the second semester of sharia economics program in STIESNU Bengkulu) - Erlangga, Pinto (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
The purpose of this research was to find out whether Kahoot Application has any effect on students' writing Skills in the Sharia Economics program at STIESNU Bengkulu. Quasi-experimental was the design of this research. The population in this research was second semester of Sharia of Economics program in STIESNU Bengkulu. The technique of this research was purposive sampling. The samples was 26 students. To collecting the data researcher used writing test. To anylzye the data used normality test and T-test. The result showed pre-test mean score was 53.54, the post-test mean score was 66.54. There was a 13-percent increase in the average value of the initial and final tests. The concluded of this research that the second semester of Sharia of Economics program in STIESNU Bengkulu demonstrated using the Kahoot Application to treat pupils had a substantial impact on their writing abilities.